The Relevance of Ki Hajar Dewantara's Educational Philosophy with Islamic Values to Form Morally Noble and Progressive Generations - Raysa Afifa Amelia; Salsabila Salsabila; Muhamad Yahya (Socrates: Journal of Education, Philosophy and Psychology, 2025)
This research investigates how Ki Hajar Dewantara's educational philosophy aligns with Islamic teachings to cultivate morally upright and progressive generations. This study addresses the declining moral standards among youth and the need for holistic education integrating local wisdom with religious values. The research novelty lies in exploring the intersection between Ki Hajar Dewantara's educational philosophy and Islamic pedagogy, an area rarely studied integratively. Using qualitative methodology with library research and hermeneutic analysis, this study examines key concepts including Tri Pusat Pendidikan (Three Centers of Education), the among system, Trikon, and Islamic education concepts (tarbiyah, ta'lim, ta'dib). The findings demonstrate strong alignment between Ki Hajar Dewantara's concept of freedom and Islam's fitrah, the among methodology (asih, asah, asuh) with prophetic teaching methods (rahmah, hikmah, mau'idzah hasanah), and Tri Pusat Pendidikan with Islamic emphasis on family, school, and community roles. This synergy can be implemented through integrated curriculum development, teacher role reinforcement, conducive educational environments, and holistic evaluation systems.